PENGARUH PENGALAMAN KERJA DAN PENDIDIKAN TERHADAP PRESTASI KERJA DAN PENGEMBANGAN KARIR KARYAWAN - MUHAMMAD HATTA NURHIDAYAT; Prof. Dr. Muhammad Saleh, MS; Dr. Gusti Noorlitaria Achmad, SE, MM (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2020)
Abstract Job Satisfaction and Employee Performance are very important for the achievement of Vision and Mission Dinas Cipta Karya dan Tata Kota Samarinda.The purpose of this research is to find out and analyze the direct influence of the Job itself, Incentives, Promotion Opportunities, Supervision, Coworkers, Working Conditions on job satisfaction and employee performance, and to know and analyze the direct influence of job satisfaction and employee performance on Dinas Cipta Karya dan Tata Kota Samarinda. The results of the study show that the Job Directly has a positive and significant effect on job satisfaction, Direct incentives have a positive but not significant effect on Job Satisfaction, Promotion Opportunities directly have a positive and significant effect on Job Satisfaction, Direct supervision has a positive and significant effect on Satisfaction Work, coworkers directly have a positive and significant effect on Job Satisfaction, Working Conditions are directly negative and not significant towards Job Satisfaction, Jobs Alone are directly positive and significant to Employee Performance, Incentives are directly positive but not significant to Employee Performance, Opportunity Promotions are directly positive and significant towards Employee Performance, Supervision directly has a positive and significant effect on Employee Performance, Cooperation Partners directly have a positive and significant effect on Ki Employee Performance, Working Conditions are directly negative and not significant to Employee Performance, Job Satisfaction is directly positive but not significant to Employee Performance.Keywords : Work Alone, Incentives, Promotion Opportunities, Supervision,       Colleagues, Working Conditions, Job Satisfaction, Employee Performance